Solanum Melongena L. Reaction to Combining Doses of PGPR Imperata Cylindrica and Cow Manure: Growth and Yield - Nareswari, Daniela Hapsari; Kristalisasi, Elisabeth Nanik; Ardiani, Fani (Journal of Agriculture, 2025)
This study aims to examine the interaction between PGPR roots of Imperata cylindrica and cow manure on the growth and yield of Solanum melongena L., and to determine the optimal dose of both treatments. The study used a factorial Completely Randomized Design (CRD) with two factors: the dose of PGPR roots of Imperata cylindrica (0, 10, 30, 50 ml) and cow manure (0, 1, 2 kg), with five replications, the data were analyzed by ANOVA at a 5% level and further tested with DMRT at a 5% level. The results showed a significant interaction between PGPR roots of Imperata cylindrica and cow manure on plant height and number of leaves, with the best results being PGPR 30 ml and cow manure 2 kg. The dose of PGPR Imperata cylindrica roots of 30 ml can increase plant height, number of leaves, fruit weight, fresh root weight, and root length. However, the dose of PGPR Imperata cylindrica roots of 50 ml can reduce the percentage of fruit wilting. The dose of 2 kg of cow manure can increase plant height, number of leaves, number of fruits, fruit weight, fresh root weight, dry root weight, and root length of plants. This study concluded that PGPR Imperata cylindrica roots and cow manure or their combination affect the growth and production of Solanum melongena L. plants.